PENGARUH PELATIHAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MASA KERJA SEBAGAI VARIABEL MODERASI (Survei pada Karyawan ARFA Barbershop Cabang Solo) - Lamidi, Daning Fitri Hafidha, SL. Triyaningsih & (Universitas Slamet Riyadi, 2016)
This study aimed to analyze the significance of the effect of training on employee performance, the effect of job satisfaction on employee performance, the effect of tenure on employee performance, the effect of training on employee performance moderated by tenure, and the effect of job satisfaction on employee performance moderated by tenure. The study population was all employees working in 8 outlets ARFA Barbershop Solo Branch, with a sample of 38 respondents. Data collection methods used are questionnaires and observation. Data were analyzed using classical assumption test and a test of the absolute value of the difference. Based on the survey results revealed that (1) Training no significant effect on the performance of employees (2) Job satisfaction significantly influence employee performance (3) The tenure of the significant effect on the performance of employees (4) The tenure of the moderating influence of training on employee performance and (5) the tenure of the moderating effect of job satisfaction on employee performance.Keywords: training, job satisfaction, tenure, employee performance